Investigating Potential Additive Effects of Formic Acid and Glycerol Monolaurate in Nursery Pig Diets - Payton L. Dahmer; Olivia L. Harrison; Cassandra K. Jones (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 350 weanling pigs (200 × 400, DNA; initially, 12.5 ± 0.3 lb BW) were used in a 42-d study with 5 pigs per pen and 14 replicate pens per treatment. At weaning, pigs were allotted to pens in a completely randomized design and pens of pigs were randomly assigned to one of five dietary treatments: 1) negative control (standard nursery diet with no additives); 2) control diet with 3,000 ppm ZnO included in phase 1 and 2,000 ppm ZnO included in phase 2; 3) control diet with 0.7% formic acid (Amasil NA, BASF, Florham, NJ); 4) control diet with 0.18% glycerol monolaurate (Natural Biologics GML, Natural Biologics, Newfield, NY); and 5) control diet with a 1.0% blend of formic acid, sodium diformate, and glycerol monolaurate (FORMI 3G, ADDCON GmbH, Bitterfeld-Wolfen, Germany). Pigs were fed treatment diets from d 0 to d 28 and were then fed a common diet from d 28 to d 42. This allowed diets to be fed as part of a standard 3-phase nursery program. From d 0 to d 7, pigs fed a diet containing ZnO or the 1.0% blend of formic acid, sodium diformate, and glycerol monolaurate had significantly increased (P= 0.03) ADG compared to pigs fed the control. Feed intake did not differ (P>0.05) during this period. Overall, pigs fed GML had reduced ADG compared to their counterparts fed the negative control, ZnO, or FORMI diets. Feed intake was also not impacted (P= 0.233) by dietary treatments. Fecal DM was evaluated from d 7 to d 28 and there was a significant treatment × day interaction (P= 0.035). Pigs fed GML had significantly lower fecal DM % on d 7, but a higher fecal DM % on d 14 and 21. There was no evidence of difference between treatments for fecal DM by d 28. In summary, there is potential for a blend of formic acid and GML to improve growth performance immediately post-weaning without negatively impacting fecal consistency. Further research is warranted to determine the mode of action of these acids and elucidate their efficacy as alternative feed ingredients to combat post-weaning challenges in swine production.
Keywords: nursery pig; formic acid; growth; fecal consistency